Pengaruh Kualitas Pelayanan Terhadap Kepuasan Siswa Pada SMA Krjp Kecamatan Rupat Kabupaten Bengkalis - M.Syamil, M.Syamil; Rizqi, Fakhri (Eko dan Bisnis: Riau Economic and Business Review, 2024)
This research was conducted at SMA KRJP, located in Rupat District, Bengkalis Regency. The purpose of this study is to determine the influence of service quality on student satisfaction at SMA KRJP. The population in this study consists of 420 students. The sample was selected using the accidental sampling method, resulting in a total of 81 respondents (simplified using the Slovin formula). To analyze the data collected, the researcher used descriptive and quantitative analysis methods. Based on the descriptive analysis results, respondents strongly agreed with the statements related to the service quality variable and also strongly agreed with the statements related to the student satisfaction variable. The results of the quantitative analysis show that service quality has a positive and significant effect on student satisfaction, as evidenced by the simple linear regression equation Y = 21.482 + 4.059X. The t-test result shows that the t-value for the service quality variable is 7.122 (greater than the t-table value of 1.990), with a significance level of 0.001 < 0.05. From the coefficient of determination test, it is known that the R² value is 39,1%, which means that the service quality variable influences student satisfaction by 39.1% at SMA KRJP, while the remaining 60.9% is influenced by other variables not examined in this study.